HEROES OF THE BATTELFIELD: THE CULT OF RUSSIAN SOLDIERS DURING THE SERBIAN-TURKISH WARS (1876–1878) IN SERBIAN 19TH CENTURY VISUAL CULTURE (Heritage, 2023)
The paper disscuses the making of the cult of Russian soldiers during the Serbian-Turskish wars (1876–1878). The making of heroes is not a spontaneous process, but a consequence of a deliberate and intentional memory making. Visual culture is an important part of that process. This paper analyses the making of the cult of Russian soldiers by focusing on the public monuments and illustrated periodicals. As in the case of  public monuments in general, which took various forms in the visual culture of the 19th century, the monuments related to the Russian soldiers were also diverse. They memorialised collective identity of Russian volunteers in First Serbian-Turkish war (1876–1877) in a from of an obelisk or of churches that represent sacral memorial places. There are also memorials of a notable individual, collonel Nikolaj Nikolajevich Rajevski, who got several cenotaphs and whose funeral became a public manifestation. Besides monuments, illustrated news also played an important role in the making of the heores. These were imortant political and cultural factors in the 19th century. As a mass media they influenced the public opinion by publishing portraits of Russian soldiers and their biographies. Beside portraits, illustrated periodicals also published war images where the colective power of the Russian army was celebrated. The pictures of hard times for the army also emphasized their heroism. A peculiar illustration showing Turkish attrocities apeared in one of the analised illustrated periodicals. This kind of picture was carefully picked with the purpouse of inducing the sympathy of the readers for the victims, in this case Russians.
Keywords: the cult of heroes, Russian soldiers, pictures of war, illustrated periodicals, monuments, Serbian-Turkish wars